2021
DOI: 10.1155/2021/1555712
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of 177Lu-PSMA-617 in Hospital Radiopharmacy: Convenient Formulation of a Clinical Dose Using a Single-Vial Freeze-Dried PSMA-617 Kit Developed In-House

Abstract: Objective. In the recent time, endoradionuclide therapy for metastatic castration-resistant prostate carcinoma employing 177Lu-PSMA-617 has yielded encouraging results and several clinical trials with the agent are currently ongoing. Routine preparation of 177Lu-PSMA-617 patient doses can be made simpler and convenient, if the ingredients essential for radiolabeling are made available in a ready-to-use lyophilized form. Methods. PSMA-617 freeze-dried kit was formulated and used for the preparation of 177Lu-PSM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Another extremely popular antioxidant used in radiopharmaceuticals is gentisic acid (2,5-dihydroxybenzoic acid, DHB). The effectiveness of gentisic acid in preventing radiolytic degradation in the final dosage form has been demonstrated for different 177 Lu-radiopharmaceuticals used in clinical practice, such as [ 177 Lu]Lu-PSMA-617, [ 177 Lu]Lu-PSMA-I&T, and [ 177 Lu]Lu-DOTATATE [ 16 , 39 , 40 , 41 , 42 , 43 ]. Furthermore, it has been shown that gentisic acid may improve the stability of radiopharmaceuticals even with α-emitting radionuclides: the addition of 0.1 M gentisic acid increases the stability of [ 225 Ac]Ac-macropa-PSMA by preventing radiolytic degradation [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another extremely popular antioxidant used in radiopharmaceuticals is gentisic acid (2,5-dihydroxybenzoic acid, DHB). The effectiveness of gentisic acid in preventing radiolytic degradation in the final dosage form has been demonstrated for different 177 Lu-radiopharmaceuticals used in clinical practice, such as [ 177 Lu]Lu-PSMA-617, [ 177 Lu]Lu-PSMA-I&T, and [ 177 Lu]Lu-DOTATATE [ 16 , 39 , 40 , 41 , 42 , 43 ]. Furthermore, it has been shown that gentisic acid may improve the stability of radiopharmaceuticals even with α-emitting radionuclides: the addition of 0.1 M gentisic acid increases the stability of [ 225 Ac]Ac-macropa-PSMA by preventing radiolytic degradation [ 44 ].…”
Section: Introductionmentioning
confidence: 99%